2018
DOI: 10.1021/acssensors.8b00224
|View full text |Cite
|
Sign up to set email alerts
|

Direct Screening for Cytometric Bead Assays for Adenosine Triphosphate

Abstract: Cytometric bead assays have caught much attention because of their many exceptional advantages. Unfortunately, the immobilization of existing molecular recognition elements including monoclonal antibodies and aptamers onto solid particles may lead to the functional failure of the molecular recognition elements since they are generally obtained in free state. Herein we develop a powerful screening approach for direct and rapid discovery of aptamer based cytometric bead assays (AB-CBAs) by individually measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The only other comparable small molecular target is probably estradiol (selected at least eight times) . Aside from what already been discussed, at least two additional DNA aptamer selections were performed, each using a different selection method. , We aligned their sequences with our new aptamers and the classical aptamer, and none of the conserved regions aligned (Figure S3). Their binding properties are compared in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…The only other comparable small molecular target is probably estradiol (selected at least eight times) . Aside from what already been discussed, at least two additional DNA aptamer selections were performed, each using a different selection method. , We aligned their sequences with our new aptamers and the classical aptamer, and none of the conserved regions aligned (Figure S3). Their binding properties are compared in Table S4.…”
Section: Resultsmentioning
confidence: 99%
“… 27 Most recently, Zheng et al reported an ATP aptamer that can be used in cytometric bead assays. 28 Although these SELEX strategies are powerful for guiding the selectivity, still no aptamers are available for highly selective binding of adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available candidates, optical recognition is the commonly effective manner because of its unique features relating to speed, intuitiveness, and controllability. Most recently, many studies have incorporated optical supports and presented their commendable abilities in bioassays. …”
mentioning
confidence: 99%